Analysis of the Influence of Governance and Social Responsibility (CSR) on Performance and Savings and Loans Welfare Cooperative - Rejeki, Sri; Usman, Bahtiar (Asian Journal of Social and Humanities, 2023)
This research aims to determine the welfare of cooperative members through governance and social responsibility (CSR) variables. The research objects are the Bererod Gratia Savings and Loans Cooperative and the Madani Savings and Loans Cooperative. Samples were taken from cooperative members who had been members of the cooperative for 3 years or more. The research uses a qualitative approach to analyze the results of the questionnaire. Analysis was carried out using content analysis. Primary data was obtained from the results of interviews and questionnaires announced to respondents. Meanwhile, secondary data was taken from the 2020-2022 Annual Member Meeting Report. The questionnaire concluded that the welfare of cooperatives depends on good, professional and sustainable governance and social responsibility (CSR). Good Corporate Governance is manifested in transparency, accountability, responsibility, independence, equality and fairness in every financial transaction, level of management commitment, quality of cooperative performance, and decision making that involves all members. Research also shows the responsibility of social cooperatives for the welfare of members and the surrounding community which has a positive influence in the form of social, economic, environmental, law-abiding, and education-health. Finally, research shows that professional quality performance by having work motivation, good financial freedom, a conducive work environment, opportunities for self-development, a strong collaborative team, and sustainable financial stability can help the welfare of cooperative members and the desire for cooperatives. The research results show that both cooperatives have succeeded in promoting the welfare of their members. Suggestions for further research include research on other cooperatives. not limited to just two cooperatives and with a wider working area coverage.